PEMANFAATAN URIN SAPI PERAH SEBAGAI PUPUK DAUN PADA RUMPUT GAJAH (Pennisetum purpureum) - BADAT M.; U. ALI; J. SUBAGYO (Majalah Ilmiah Peternakan, 2021)
The study aimed at knowing the effects of urine fertilizing and effects interaction between urine concentration and fertilizing frequency to production and quality of elephant grass. The experiment used completely random design (RAL) with factorial pattern (3 x 3), first factor was urine concentration in water, 5%, 7.5%, 10% and second factor was fertilizing frequency 1 times, 2 times and 3 times during cutting interval. Observation undertaken to fresh production and dry matter (DM), content of DM, Organic Matter (OM), Crude Protein (CP) and Crude Fiber (CF). Result of the study could be concluded that exploitation of urine as leaf fertilizer could increase production and quality of elephant grass. Interaction between Urine concentration and frequency fertilizing was significantly affected to fresh production and BK. Away from this affected to enhance content of OM, CP and decreased content of CF, but it was not significantly affected to content of DM of elephant grass. The highest fresh production of 19.33 kg/m2 and the highest DM production 2.58 kg/m2 both obtained at treatment K3F3. Content of OM, highest CP and content of lowest CF by effects of enhancement of urine concentration were 83.96%, 10.14% and 35.00%. While effects of fertilizing frequency were 83.84%, 9.26% and 35.70%.